2021
DOI: 10.1371/journal.ppat.1009223
|View full text |Cite
|
Sign up to set email alerts
|

The leucine-rich repeats in allelic barley MLA immune receptors define specificity towards sequence-unrelated powdery mildew avirulence effectors with a predicted common RNase-like fold

Abstract: Nucleotide-binding domain leucine-rich repeat-containing receptors (NLRs) in plants can detect avirulence (AVR) effectors of pathogenic microbes. The Mildew locus a (Mla) NLR gene has been shown to confer resistance against diverse fungal pathogens in cereal crops. In barley, Mla has undergone allelic diversification in the host population and confers isolate-specific immunity against the powdery mildew-causing fungal pathogen Blumeria graminis forma specialis hordei (Bgh). We previously isolated the Bgh effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 66 publications
1
82
0
Order By: Relevance
“…For example, for Pm3a with an amino acid exchange in the C‐terminal LRR27 the Pm3a‐δ5 mutant showed a lower activation threshold than the natural Pm3a and an expanded recognition spectrum towards naturally occurring AvrPm3 A2/F2 variants (Lindner et al ., 2020). The LRR swaps between the barley Mla1 and Mla6 (Shen et al ., 2003; Bauer et al ., 2021), as well as swaps between Mla10 and Mla22 (Bauer et al ., 2021) demonstrated that the effector recognition specificities are determined by the C‐terminal LRRs of the Mla proteins. The LRR swaps between either the flax L6 and L11 or L5 and L6 variants revealed that the last four LRRs of L6 are required for the recognition of the flax rust effector AvrL567‐D (Ellis et al ., 2007; Ravensdale et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for Pm3a with an amino acid exchange in the C‐terminal LRR27 the Pm3a‐δ5 mutant showed a lower activation threshold than the natural Pm3a and an expanded recognition spectrum towards naturally occurring AvrPm3 A2/F2 variants (Lindner et al ., 2020). The LRR swaps between the barley Mla1 and Mla6 (Shen et al ., 2003; Bauer et al ., 2021), as well as swaps between Mla10 and Mla22 (Bauer et al ., 2021) demonstrated that the effector recognition specificities are determined by the C‐terminal LRRs of the Mla proteins. The LRR swaps between either the flax L6 and L11 or L5 and L6 variants revealed that the last four LRRs of L6 are required for the recognition of the flax rust effector AvrL567‐D (Ellis et al ., 2007; Ravensdale et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a mutagenesis study on AvrL567 using amino acid polymorphisms across the allelic variants led to the identification of three amino acids involved in the recognition by the L proteins and suggested that the specificity is a result of the additive effect of multiple contact points with the L protein (Dodds et al ., 2006; Ravensdale et al ., 2012). Chimeric effectors between Avra10 and Avra22 demonstrated that four (Avra10) and five (Avra22) amino acids are necessary to confer Mla10‐ and Mla22‐specific recognition, respectively (Bauer et al ., 2021). These findings suggest that multiple amino acids on the Avra effector surface determine the recognition specificities of Mla proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of Bgh CSEPs (c. 25%) are structurally predicted similar to RNase and/or RNA-binding activity, and these CSEPs are termed as RNase Like Proteins expressed in Haustoria (RALPHs) ( Pedersen et al, 2012 ; Spanu, 2017 ). Interestingly, most of the so far identified Bgh AVR A effectors, each recognized by a cognate barley MLA receptor, are also RALPHs with fungal RNase folds but lacking the residues required for RNase activity ( Lu et al, 2016 ; Saur et al, 2019 ; Bauer et al, 2021 ). So far, several Bgh CSEPs/BECs have been functionally characterized with respect to fungal virulence through transient gene expression and host-induced gene silencing (HIGS) approaches ( Bindschedler et al, 2009 ; Godfrey et al, 2009 ; Nowara et al, 2010 ; Spanu et al, 2010 ; Pedersen et al, 2012 ; Pliego et al, 2013 ; Ahmed et al, 2015 , 2016 ; Menardo et al, 2017 ; Frantzeskakis et al, 2018 ; Pennington et al, 2019 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the interaction between Blumeria graminis f. sp. hordei (Bgh), the causal agent of powdery mildew, and its cereal host plant, barley (Hordeum vulgare L.), disease is blocked by the action of specific barley R-proteins, designated ML, that respond to corresponding Bgh effectors, designated AVR (Lu et al, 2016;Saur et al, 2019;Bauer et al, 2021;Ridout et al, 2006). Diversification of the Mla NLR (Wei et al, 2002;Seeholzer et al, 2010), has generated up to 30 allelic variants that confer specific recognition to different AVR-associated Bgh isolates (Lu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%